Promoting Digital Well-Being Through English Graffiti Art: A Case Study of Junior High School Students - Widia Fransiska; Meida Rabia Sihite; Linda Astuti Rangkuti; Iskandar Zulkarnain (Universitas Islam Negeri Palopo, 2026)
Unhealthy digital habits among junior high school students, including excessive gaming and prolonged social media use, have raised concerns about their impact on students’ creativity, focus, and real-world interaction. This study investigates the role of English graffiti art as an innovative pedagogical approach to shaping healthier digital practices among students at a private junior high school in Medan. Employing a qualitative case study design, the research was conducted with three classes of seventh-grade students who participated in classroom activities that integrated graffiti art into English language learning. Data were collected through preliminary surveys documenting students’ digital habits, student-created artifacts reflecting awareness and attitudes toward technology use, classroom observations capturing engagement and collaboration, and reflective journals and interviews with students and teachers, providing deeper insights into their perceptions. Quantitative data from surveys were analyzed using descriptive statistics to identify students’ awareness of their digital healthy habits. Triangulation of findings across multiple sources strengthened the validity of interpretations. Results indicate that integrating graffiti art into English learning can raise students’ awareness of their digital behaviors, encourage creative expression, and promote more balanced technology use. The study concludes that arts-based pedagogy offers meaningful potential not only for enhancing linguistic and creative skills but also for addressing contemporary challenges in students’ digital well-being.